(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Innovation is crucial for entrepreneurship, and it is important to comprehend the aspects that contribute to the effectiveness of new companies in order to establish strong and prosperous ventures. Startups can successfully negotiate the challenges of the business landscape and prosper in the pursuit of innovation by adopting visionary leadership, adaptability, customer focus, teamwork, risk-taking, technology adoption, efficient resource management, and a culture of continuous learning. Entrepreneurship is fundamentally centered around recognizing prospects, embracing uncertainties, and generating worth. Innovation functions as the driving force that propels entrepreneurs ahead, empowering them to establish a distinct position in the market and adapt to evolving consumer demands. In today’s business world, which is marked by fast-paced technology progress and global interconnectivity, the significance of innovation cannot be emphasized enough. Newly created companies, known for their ability to quickly adapt and question old conventions, have a distinct advantage in adopting and utilizing innovation. These emerging businesses offer a new viewpoint to the market, free from conventional frameworks and procedures. Nevertheless, the triumph of these fledgling companies is not assured, and comprehending the elements that contribute to their effectiveness is crucial for prospective entrepreneurs and individuals engaged in bolstering startup ecosystems. The main aim of the research is to study significance of innovation in entrepreneurship in relation to the efficacy of fresh startups & to examine the effectiveness of different variable factors of Entrepreneurship on contribution to the efficacy of fresh start-up factors.